Investigation and comparison of four new types of damper (Journal of Civil Engineering Researchers, 2020)
The unfavorable experience of the past earthquakes and their respective financial and human loss indicates the weak seismicperformance of some buildings. Hence, employing new equipment and tools is inevitable in this respect. The first idea is amulti-level passive control system able to shift the dynamic behavior parameters such as stiffness, strength, and damping ratioto absorb the seismic energy on multiple levels. This system is made up of a combination of nested pipe componentsabsorbing energy during moderate and intense earthquakes. The second idea of the paper constitutes a new metal slit dampermade of metal plates with high elevation whose metal parts are connected. The weak slit damper part is designed to workduring low to moderate seismic induction, while the strong slit damper section is designed to be activated during largeearthquakes. Another study examines the seismic behavior of a new type of damper consisting of U-shaped steel plates asenergy-dissipating elements empirically, and the last study explores the performance of U-shaped yielding steel dampers insteel building frames. The present paper reviews and compares four types of introduced dampers
Keywords: Ductility; damper; Nonlinear dynamic analysis; U-shaped damper; Hysteretic dampers; Multi-level control system